Settlement analysis of friction piles in consolidating soft soils (2015)
The paper shows how axisymmetric finite element numerical models can be used to optimize the design of friction piles foundations in an environment that is prone to regional subsidence. The study considers friction piles in typical Mexico City soft clays, that are subjected to external loads and soil consolidation due to variations in piezometric conditions. The constitutive models used to numerically simulate the behavior of the clays vary from a basic elastic perfectly-plastic model to a critical state model that is able to account for the anisotropic yielding behavior of Mexico City clay. The simulations consider the long term behavior of the internal piles within a large pile group.